Viitor Gaming Chair / Akmal Haziq Ahmad Aizam - Ahmad Aizam, Akmal Haziq; Tajaludin, Abdul Muhaimin; Husaini, Nur Sabrina; Aminuddin, Muhammad Haiman; Khairuddin, Fais Syamir (2022)
The process of introducing new products and the product development that were produced to promote into the market is known as new product development. It entails several processes that must be performed before the product's launch and exposure to the market. Any business that wants to stay up with market trends and changes must produce new products. The basic introduction of the new product development, as well as the issue and technique of the product, have been mentioned in this section of the research project. The project's goals are to indicate how to enhance and innovate a current gaming chair into a multi-function gaming chair that may benefit users. Furthermore, we discussed the product development process, which may be divided into five steps: research and development (idea creation and idea screening), product design or feature, concept testing, prototype creation/build, and test marketing. Finally, we used the Customer Trend Canvas (CTC) analysis to study the product and identify the fundamental demands, inspirations, innovation potential, and developing consumer expectations, as well as determine a solution that can be applied in the project to address the present challenges. To further expand a business or any organization, it is important to have a strategy and plan in place to enhance the current old system. Concept testing and market research were undertaken via a Google Form that was made public to enhance and innovate the product and to meet the requirements and desires of consumers.